Iatrogenic bile duct injury repair using isolated vascularized gastric tube: early experience in two tertiary centers - Helmy, Ashraf A.; Ali, Ayman M. A. (International Surgery Journal, 2017)
Background: Bile duct injuries (BDI) constitute a disaster for both the patient and the surgeon without satisfactory results with the classic use of roux-en-Y hepaticojejunostomy (RYHJ). The purpose of this study was to evaluate our newly introduced technique utilizing isolated vascularized gastric tube (IVGT) as an alternative for RYHJ in reconstruction of the bile duct after iatrogenic BDI with lost segment. Methods: This is a prospective study included 18 consecutive patients suffered from iatrogenic BDI with lost segment admitted to Assiut and Sohag University Hospitals, during the period from September 2013 to June 2016. Patients were subjected to operative treatment with the interposition of IVGT to bridge the lost bile duct segment. Patients were evaluated regarding demographic criteria, clinical picture, different investigations, efficacy of the use of IVGT and evaluation of post-operative complications after a mean follow-up of 2 years. Results: Eighteen patients underwent repair of BDI utilizing IVGT during the study period. Three patients (17%) suffered immediate repairs, 10 patients (55%) experienced intermediate repairs and late repairs were performed for the last 5 patients (28%). Bile leak as a specific early morbidity was present in 3 patients (17%) with upper biliary tract injury without any operative mortality. Also, there was one patient with stent obstruction relieved by stent extraction. With long-term follow-up there was not any patient of biliary stricture. Conclusions: IVGT proved to be feasible and safe for bile duct replacement and is a good alternative for biliary reconstruction being more anatomical and physiological than RYHJ.